Support to Aging Parents and Grown Children in Black and White Families - Fingerman, Karen L. (Oxford University Press, 2011)
Purpose: Black and White middle-aged adults typically are in a pivot position of providing support to generations above and below. Racial differences in support to each generation in the family remain unclear, however. Different factors may account for racial differences in support of grown children versus aging parents. Design and Methods: Middle-aged adults (aged 40–60 years; 35%, n = 216 Black and 65%, n = 397 White) rated social support they provided each aging parent and grown child. Participants reported background characteristics representing their resources and measures of needs for each family member. Interviews also assessed beliefs about obligation to support parents and grown children and rewards from helping. Results: Multilevel models revealed White middle-aged adults provided more support to grown children than Black middle-aged adults. Demands from offspring, beliefs about support, and rewards from helping explained these racial differences. Black middle-aged adults provided more support to parents than White middle-aged adults. Beliefs about support and feelings of personal reward from providing support explained this difference but resources and demands did not. Implications: Racial differences varied by generation (parent or offspring). The prolonged transitions common for White young adults explained racial differences in support of offspring. Middle-aged adults may treat support of parents as more discretionary, with cultural ideas about obligation and personal rewards guiding behaviors.